Manajemen Mutu Pendidikan Pondok Pesantren Nurul Huda Pragaan Sumenep Di Era 5.0 - Zeinal Abidin; Rinta Ratnawati (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to determine the educational management of the Nurul Huda Islamic boarding school in the 5.0 era. The research method used is descriptive with a qualitative approach, with the research object being the Nurul Huda Islamic Boarding School. Data analysis used analysis before in the field and during the field such as data reduction, data presentation, and Conclusion Drawing/Verification. Data collection procedures commonly used are observation, interviews, and documentation. The results of the research show that in implementing the quality management of Islamic boarding schools, cooperation, and mutual reminders are needed so that the work programs that have been designed continue to improve so that the quality of Islamic boarding school education and graduates will be great. There are several supporting and inhibiting factors in the implementation of quality management in Islamic boarding schools, namely lack of awareness of the management in carrying out the tasks and responsibilities that have been given because they are busy with their interests, teachers are less active in teaching and often neglect the work program that has been designed. so that in its implementation many work programs were neglected. In conclusion, the quality management of Islamic boarding school education needs to be formulated carefully to be able to produce quality educational output. Keywords: Education Quality Management, Islamic Boarding School, era 5.0